2020
DOI: 10.1136/bmjdrc-2019-001149
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic insulin clearance is increased in patients with high HbA1c type 2 diabetes: a preliminary report

Abstract: IntroductionHepatic insulin clearance (HIC) is an important pathophysiology of type 2 diabetes. HIC was reported to decrease in patients with type 2 diabetes and metabolic syndrome. However, hyperglycemia was suggested to enhance HIC, and it is not known whether poorly controlled diabetes increases HIC in patients with type 2 diabetes. We investigated whether HIC was increased in patients with poorly controlled diabetes, and whether HIC was associated with insulin resistance and incretins.Research design and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…In a previous study, it was shown that glucagon may be inversely related to insulin clearance [36]. It is also worth noting that, in our previous study on incretin hormone single knockouts, we found different glucagon secretion levels depending on the deleted incretin hormone receptor [34].…”
Section: Discussionmentioning
confidence: 52%
“…In a previous study, it was shown that glucagon may be inversely related to insulin clearance [36]. It is also worth noting that, in our previous study on incretin hormone single knockouts, we found different glucagon secretion levels depending on the deleted incretin hormone receptor [34].…”
Section: Discussionmentioning
confidence: 52%
“…The glucose clamp method was performed as we previously reported 8 , 19 . We performed the hyperinsulinemic-euglycemic clamp method to evaluate insulin sensitivity with an artificial endocrine pancreas (STG 55, Nikkiso, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…One study reported that SGLT2i treatment increased insulin clearance after the meal tolerance test 7 . However, we previously reported that Japanese patients with poorly controlled T2DM showed increased hepatic insulin clearance 8 .…”
Section: Introductionmentioning
confidence: 96%
“…Over the past several decades, numerous studies have identified type 2 diabetes mellitus (T2DM) [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ] and obesity [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ] as determinant factors associated with impaired insulin clearance. Other metabolic abnormalities, such as non-alcoholic steatohepatitis [ 77 , 92 , 93 , 94 , 95 ], hepatic diseases [ 96 , 97 , 98 , 99 ], polycystic ovarian syndrome [ 100 ], and metabolic syndrome [ 101 , 102 ], as well as aging [ 78 , 103 , 104 ] and ethnicity [ 105 , 106 , 107 , 108 , 109 , 110 , 111 ], have also been linked to reduced insulin clearance.…”
Section: Introductionmentioning
confidence: 99%